Sex, Lies, and Stereotypes: Gendered Implications of Fake News for Women in Politics. (3rd September 2019) - Stabile, Bonnie; Grant, Aubrey; Purohit, Hemant; Harris, Kelsey
Abstract : This analysis examines the literature on gendered media coverage of women candidates for higher office, and considers how biases in the treatment of candidates based on gender may be evident in or exacerbated by the promulgation of fake news. Using the 2016 Presidential election cycle in the United States as a case study, two fake news stories are investigated, which, like most fake news stories at the time, exhibited coverage in favor of the candidacy of Donald Trump and demonized or denigrated his opponent, Hillary Clinton. Findings suggest that the Pizzagate and Hillary Health Scare stories evince gendered narratives supporting stereotypes of women as unfit for leadership positions, and either villainize or trivialize women, depending on their perceived degree of power. Using a dataset of news articles and tweets from the months surrounding the 2016 election, evidence is offered of more negative coverage of the female versus male contender, in keeping with the findings of the literature, though the presence of potentially confounding factors, including personality and party, is acknowledged.